The Swiss legal system on advance requests for assisted suicide from persons without the capacity of judgement - Hotz, Sandra (My University, 2026)
Cet article décrit le système juridique suisse applicable aux questions relatives à la fin de vie. Il présente le cadre actuel, en mettant l’accent sur la question des demandes anticipées d’assistance au suicide émanant de personnes incapables de discernement et atteintes de démence. Plus précisément, l’autrice soutient que ce cadre devrait être adapté, en tenant davantage compte du droit civil et du droit de la santé, tout en s’inspirant des législations étrangères.

This article describes the Swiss legal rules applying to end-of-life issues. It presents the current framework, with a focus on advance directives for assisted suicide from persons without the capacity of judgement. More specifically, the author argues that this framework should be improved by reforming criminal law and taking greater account of civil law and health law, drawing inspiration from foreign legislation.
Keywords: Suicide assisté – Euthanasie – Suisse – Droit pénal – Directives anticipées – Décisions de fin de vie – Autonomie – Droit médical.